VALIDITY OF STEM INTEGRATED STATIC FLUID E-MODULE TO IMPROVE STUDENT LEARNING OUTCOMES - Aprina Maharani Zuna Arnis Nasution; Asrizal Asrizal; Festiyed Festiyed; Renol Afrizon (Universitas Negeri Padang, 2022)
The rapid development of technology and information brings many impacts in various fields, especially in the field of education. Student learning activities with digital technology in learning cannot be separated, so students are expected to master technology such as electronic modules. Student learning outcomes seen from the final semester exams for class XI MIPA students are quite adequate with an average score of 5 classes, namely 62, so it is necessary to follow up with the manufacture of STEM integrated static fluid electronic modules to improve student learning outcomes. The purpose of this study was to determine the validity of the STEM integrated module with professional static fluid material flip pdf software. The research method used by Hannafin and Peck's instructional development model is focused on product-oriented learning design. The instrument used in the study was an electronic module validation sheet that involved 5 lecturers as product validators. Data analysis showed that the development of electronic teaching materials scored 85.63 which belonged to the category of good use. Therefore, the design of the STEM-integrated static fluid material electronic module can help online learning activities during the pandemic. Furthermore, this study is suggested to investigate the practicality and effectiveness of electronic modules.